2002
DOI: 10.1021/ma020393h
|View full text |Cite
|
Sign up to set email alerts
|

Diffusional Behavior of Polypeptides in the Isotropic, Biphasic, and Liquid Crystalline Phases As Studied by the Pulse Field-Gradient Spin−Echo1H NMR Method

Abstract: The self-diffusion coefficients (D) of R-helical poly(n-octadecyl L-glutamate) (POLG) and chloroform (CHCl3) as solvent in the isotropic, biphasic, and liquid crystalline phases were measured as a function of POLG concentration at 30°C by the pulse field-gradient spin-echo 1 H NMR method and the diffusion 1 H NMR imaging method, to elucidate diffusional behavior of the polypeptide and solvent. From the experimental results, it was found that the diffusion coefficient of POLG is largely decreased in going from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…The diffusion coefficients, and thus, the mobility of the entire poly(g-octadecyl-l-Glu) helix were measured by means of the pulse-field-gradient spin-echo 1 H NMR method (PFG SE). [238] These measurements were conducted in chloroform solution at 30 8C in the isotropic phase, in a biphasic region, and in the cholesteric phase. The diffusion coefficient considerably decreased in this order, and the diffusion parallel to the a-helix axis was significantly higher than perpendicular.…”
Section: Liquid-crystalline Polypeptidesmentioning
confidence: 99%
“…The diffusion coefficients, and thus, the mobility of the entire poly(g-octadecyl-l-Glu) helix were measured by means of the pulse-field-gradient spin-echo 1 H NMR method (PFG SE). [238] These measurements were conducted in chloroform solution at 30 8C in the isotropic phase, in a biphasic region, and in the cholesteric phase. The diffusion coefficient considerably decreased in this order, and the diffusion parallel to the a-helix axis was significantly higher than perpendicular.…”
Section: Liquid-crystalline Polypeptidesmentioning
confidence: 99%
“…Andererseits gelang es mit der PFGSE-1 H-NMR-Methode (pulse field-gradient spin-echo), [238] Diffusionskoeffizienten und somit die Beweglichkeit der gesamten Poly(g-octadecyl-l-Glu)-Helix zu messen. Diese Messungen wurden in Chloroform an isotropen, zweiphasigen und cholesterischen Lösungen durchgeführt.…”
Section: Flüssigkristalline Polypeptideunclassified
“…Kishi et al14, 15 prepared PBLG gels in cholesteric and nematic liquid‐crystalline phases and then studied the properties of the obtained gels. In our previous works, it has been reported that a highly oriented PBLG gel can be prepared by the crosslinking reaction of highly oriented PBLG chains with a crosslinker in the magnetic field of an NMR magnet through the monitoring of the orientation of the PBLG chains with solid‐state static 13 C‐NMR;16 then, solvents and rodlike molecules in the PBLG gel anisotropically diffuse in the directions parallel and perpendicular to the α‐helix axis by a high‐field‐gradient NMR system 16–24. This shows that there exist long channels with small diameters of 15–20 Å in the highly oriented PBLG gel.…”
Section: Introductionmentioning
confidence: 97%